3-Chlorotyrosine formation in gilthead seabream (Sparus aurata) and European plaice (Pleuronectes platessa) fillets treated with sodium hypochlorite. (March 2015) - Bao Loan, Huynh Nguyen; Devlieghere, Frank; Van Hoeke, Caroline; De Meulenaer, Bruno
Abstract: The chlorination of tyrosine in fish fillets as a result of hypochlorite dipping was investigated and the formation of 3-chlorotyrosine was proved to be reproducible (average RSD < 6.0%). In European plaice, 0.85% (inner portion) and 1.88% (surface) of tyrosine were converted to 3-chlorotyrosine after 60 min dipping in 2000 mg/L NaOCl. As the dose of hypochlorite acid increased to 7816 mg/L, those percentages were 1.07% and 2.81%, respectively. Experiments on gilthead seabream showed the clear impact of dipping time and NaOCl concentration on the formation of 3-chlorotyrosine at the fillet surface and the levels of 3-chlorotyrosine reached a plateau at 1000 mg NaOCl/L. At the same dipping time, the 3-chlorotyrosine contents increased noticeably from about 1.40 to 4.90 ppm in gilthead seabream fillets treated with 125–1000 mg/L NaOCl. 3-chlorotyrosine formation was evaluated in four fish species (whiting, European plaice, gilthead seabream and Atlantic salmon) and proved to be species dependent, but no direct with the fat content could be found. During the chilled storage (4 °C), the 3-chlorotyrosine was constant. The use of 31 mg OClˉ/L could be detected for seabream. Highlights: 3-chlorotyrosine and its potential to serve as a reliable indicator to detect chlorine use on fish fillets was investigated. A clear impact of dipping time and NaOCl concentration on the formation of 3-chlorotyrosine was observed. There was no direct link between the fat content in fish flesh and the final 3-chlorotyrosine content. During the chilled storage (4°C), the 3-chlorotyrosine content was constant.